Surface modification of polyurethane with acrylamide by plasma radiation and its cellular investigations - Soleimannejad Najafabadi, Mostafa; Khorasani, Mohammad Taghi (Biomedical & pharmacology journal, 2012)
Poly urethane as a biomaterial used for medical applications. In this study, polyurethane surface grafted with to acrylamide by oxygen plasma radiation. Grafted surface were investigated by ATR-FTIR, SEM, Zeta potential and cell culture analyses. ATR-FTIR results and SEM images showed presence of acrylamide groups and successful grafting on the polyurethane surface. Cellular culture results showed more adhesive and proliferate of fibroblast cells on the acrylamide grafted polyurethane surface than the control groups. The acrylamide grafted polyurethane surface can be used for tissue engineering and medical applications.